2006
DOI: 10.1002/ijc.21892
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk among patients with condylomata acuminata

Abstract: Condylomata acuminata have been shown to increase the risk of anogenital cancers. However, previous studies have been of limited sample size and/or short follow-up duration, which prevent precise estimates of long-term excess risk, especially for specific cancer sites. We estimated the risk of specific cancers in a large cohort of hospitalized patients with condylomata acuminata, as recorded in the Swedish Inpatient Register between 1965 and 1999. Altogether, 10,971 patients (1,685 men and 9,286 women) were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 67 publications
(78 reference statements)
3
45
0
6
Order By: Relevance
“…33Y35 This is suggested to be the main reason for an increased (pre-) cancer risk among those women. 36,37 Blomberg et al 38 found that individuals with genital warts not only have an elevated risk of anogenital cancer but also for head-and-neck cancer. The authors suggest that patients with genital warts differ from the general population, with risk factors other than HPV putting them at increased risk for several cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…33Y35 This is suggested to be the main reason for an increased (pre-) cancer risk among those women. 36,37 Blomberg et al 38 found that individuals with genital warts not only have an elevated risk of anogenital cancer but also for head-and-neck cancer. The authors suggest that patients with genital warts differ from the general population, with risk factors other than HPV putting them at increased risk for several cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Sobre a infecção na região genital existem poucos estudos. Torna-se relevante identificar a infecção epitelial genital pelo EBV, bem como a possível coinfecção com o HPV, principal agente associado ao desenvolvimento de lesões intraepiteliais e carcinomas escamosos genitais (17,19) . O imunocomprometimento relacionado com o vírus da imunodeficiência humana do tipo 1 (HIV-1) é sabidamente um fator de aumento do risco para a carcinogênese genital, assim, torna-se relevante verificar possíveis diferenças entre os pacientes (13,15) .…”
Section: Investigation Of the Lmp1 Ebv And Co-infection By Hpv In Genunclassified
“…Self-inoculation has been suggested in HPV-positive Bowen's disease of the digital nail bed (15). Interestingly, it has been reported in epidemiological studies from Sweden and Denmark, that the incidence of anal and oral cavity cancers is approximately 10-and 4-fold higher, respectively, in patients with a hospital record of genital warts (16,17). Additionally, an American study showed that MSM who have had anal warts had a 50-fold higher risk of developing anal cancer (18).…”
mentioning
confidence: 99%